2007
DOI: 10.1134/s1087659607020046
|View full text |Cite
|
Sign up to set email alerts
|

Specific features of the formation of a porous structure in products of leaching of two-phase sodium borosilicate glasses in acid-salt solutions

Abstract: This paper reports on the results of an investigation into the influence of the addition of a KCl salt to an HCl acid solution on the leaching kinetics of two-phase sodium borosilicate glasses and on the structural parameters of the leaching products (porous glasses). The contributions from different molecular species of silica to its total amount in leaching solutions are evaluated using the kinetic spectrophotometric technique for determining silicon in the form of β -silicomolybdic heteropoly acid. It is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Here, the formation of the porous glass structure is associated with the polymerization of secondary silica. This process underlies the complex mechanisms of the coagulation and gelation of silica and can occur upon the collision of silica particles with a sufficiently low surface charge [16]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the formation of the porous glass structure is associated with the polymerization of secondary silica. This process underlies the complex mechanisms of the coagulation and gelation of silica and can occur upon the collision of silica particles with a sufficiently low surface charge [16]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the leaching conditions (i.e., acidic concentration, time of leaching and addition of basic solution) have also been investigated [5,6,9,[12][13][14][15][16]. It has been established that the hydrochloric acid (HCl) concentration and the leaching treatment time leads to the transformation of the micro-and mesoporous structure of porous glasses.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the data obtained has revealed that the addition of KCl to the leaching solution in contact with alkali borosilicate glasses containing the additives K 2 O (NK-3) or K 2 O and PbO (NKS-1), as in the case of the glass without additives, results in a rapid polymerization with the formation of weakly structured silica. This can be clearly seen from a comparison of the data on the silica distribution over molecular forms [3] with the structural parameters of the porous glasses SHORT COMMUNICATIONS (Table 2). A considerable increase in the specific surface area of the nanoporous glasses is accompanied by the disappearance of the polymer forms of silica in the solution.…”
mentioning
confidence: 85%
“…Glass samples in the form of polished disks 34.5 mm in diameter and 2 mm in thickness were suspended (immersed) by a platinum wire in acid solutions and leached without stirring in the course of boiling. The initial ratio of the glass surface area to the solution volume was 0.04 cm -1 , which provided a constant pH value of the solution during the experiment.In the solutions formed after through acid leaching of the samples, the kinetics of complex reactions with 1 This paper was presented at the Topical Meeting of the European Ceramic Society "Structural Chemistry of Partially Ordered Systems, Nanoparticles, and Nanocomposites," St. Petersburg, Russia, June 27-29, 2006. the participation of silica passed from the unstable phase of the glass into the solution was investigated according to the procedure described in [3,4]. The contribution from different molecular forms of silica to the total amount of this component in the solution was determined from the results of the kinetic spectrophotometric analysis for the presence of silicon in the form of β -silicomolybdic heteropoly acid (the error in the determination of the silicon content was ± 0.1 [5]).…”
mentioning
confidence: 99%
See 1 more Smart Citation